STUDI EKSTRAK n-HEKSANA DARI KULIT BATANG KANDIS HUTAN (Garcinia cymosa) - Darwati; Nurlelasari; Tri Mayanti; Unang Supratman (Jurnal Penelitian Hasil Hutan, 2021)
Plants of Garcinia genera (Fam: Guttiferae) that grows in Indonesia's tropical forests are potential of triterpenoidcompounds contents. Garcinia cymosa has been reported as the main source of triterpenoid compounds whichprovided useful biological activity such as anti-inflammatory, antibacterial, antifungal, antioxidant, cytotoxic, andanti-HIV. Currently, data and information of triterpenoid compounds in the G. cymosa is relatively low. Thispaper studies triterpenoid compound of G. cymosa. This compound was obtained from macerated G. cymosa stembark using n-hexane solvent. G. cymosa bark was macerated using n-hexsana solution, which was them separatedand purified by chromatography method, to produce pure isolate in the form of white needle crystals (10.8 mg). Thechemical structure was then determmined by using spectroscopy methods of IR, 1D-NMR, 2D-NMR, and massspectroscopy compared with published structure. Result show friedelin compound was succesfully isolated from extractedn-heksana of G. cymosa bark.